Implementation of Good Governance Principles in Rancapaku Village, Padakembang District, Tasikmalaya Regency - Hidayat, Agus Fatah (GoAcademica Research & Publishing, 2024)
This research was conducted due to problems related to the not yet optimal Rancapaku Village Government in implementing the principles of good governance. The purpose of this study is to find out and describe how the Rancapaku Village Government applies the principles of good governance so that if there are problems or obstacles encountered, the right solution can be found. This study uses research methods with a descriptive qualitative approach so that in collecting data by interviews and observation as well as documentation to produce primary data and secondary data. Meanwhile, to test the validity of the data, namely by triangulating the data so that the resulting data is not subject to data manipulation. Based on the research results, it was found that the application of the principles of good governance in Rancapaku Village, Padakembang District, Tasikmalaya Regency was analyzed using theory according to the National Development Planning Agency (BAPPENAS), namely transparency, accountability and participation which measure that the application of the principles of good Governance in Rancapaku Village has not been implemented optimally where there are still obstacles faced by the Rancapaku Village Government. So it can be concluded that to support the application of the principles of Good Governance it is very important to pay attention to the leadership style of the Village Government and administration of government which includes government services, appropriate development, and the responsiveness of the Rancapaku Village Government in overcoming problems in the community.